Methylation and expression of glucocorticoid receptor exon-1 variants and FKBP5 in teenage suicide-completers - Rizavi, Hooriyah S.; Khan, Omar S.; Zhang, Hui; Bhaumik, Runa; Grayson, Dennis R.; Pandey, Ghanshyam N. (Translational psychiatry, 2023)
A dysregulated hypothalamic-pituitary-adrenal (HPA) axis has repeatedly been demonstrated to play a fundamental role in psychiatric disorders and suicide, yet the mechanisms underlying this dysregulation are not clear. Decreased expression of the glucocorticoid receptor (GR) gene, which is also susceptible to epigenetic modulation, is a strong indicator of impaired HPA axis control. In the context of teenage suicide-completers, we have systematically analyzed the 5’UTR of the GR gene to determine the expression levels of all GR exon-1 transcript variants and their epigenetic state. We also measured the expression and the epigenetic state of the FK506-binding protein 51 (FKBP5/FKBP51), an important modulator of GR activity. Furthermore, steady-state DNA methylation levels depend upon the interplay between enzymes that promote DNA methylation and demethylation activities, thus we analyzed DNA methyltransferases (DNMTs), ten-eleven translocation enzymes (TETs), and growth arrest- and DNA-damage-inducible proteins (GADD45). Focusing on both the prefrontal cortex (PFC) and hippocampus, our results show decreased expression in specific GR exon-1 variants and a strong correlation of DNA methylation changes with gene expression in the PFC. FKBP5 expression is also increased in both areas suggesting a decreased GR sensitivity to cortisol binding. We also identified aberrant expression of DNA methylating and demethylating enzymes in both brain regions. These findings enhance our understanding of the complex transcriptional regulation of GR, providing evidence of epigenetically mediated reprogramming of the GR gene, which could lead to possible epigenetic influences that result in lasting modifications underlying an individual’s overall HPA axis response and resilience to stress.